2019
DOI: 10.3390/su11041128
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Perceived Ease of Use and Continuance Usage of a Mobile Terminal: Mobility as a Moderator

Abstract: As the number of mobile terminal users has increased worldwide, research on continuance usage of a mobile terminal (CUMT) has received wide attention to facilitate the sustainability of development of mobile application providers. However, different results of the relationship between perceived ease of use (PEU) and continuance usage toward information technology were found in prior studies, and studies that mainly focus on their linear relationship cannot provide an explanation of the different results. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
3
5
0
Order By: Relevance
“…This result might have also fostered higher levels of DSM reported in the post-intervention, because studies have demonstrated a positive association between higher levels of acceptability of a mHealth and self-management [33,70]. Likewise, perceived ease of use and satisfaction with health apps positively affect continued intention of use [71]. These were reflected in our study, as participants expressed overall satisfaction with the simplicity of MCH with intentions of continued use and recommendation to others.…”
Section: Acceptabilitysupporting
confidence: 51%
“…This result might have also fostered higher levels of DSM reported in the post-intervention, because studies have demonstrated a positive association between higher levels of acceptability of a mHealth and self-management [33,70]. Likewise, perceived ease of use and satisfaction with health apps positively affect continued intention of use [71]. These were reflected in our study, as participants expressed overall satisfaction with the simplicity of MCH with intentions of continued use and recommendation to others.…”
Section: Acceptabilitysupporting
confidence: 51%
“…Findings also confirmed H2, PEOU of the smartphone is positively related to the intention to use a smartphone for learning. Several past studies have investigated the PEOU variable in a different context (Abdullah, Ward, & Ahmed, ; Amin, Rezaei, & Abolghasemi, ; J. Lee, Ryu, & Lee, ; Li, Sun, Yang, & Guo, ; Pookulangara & Koesler, ). For example, Pookulangara and Koesler () found that PEOU is positively related to the intention to use social networking.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the main page of a smartphone application should be user‐friendly enough to improve user a good experience, such as fast response and utility. Furthermore, several functions of smartphone applications are idle, which consume memory of mobile devices; mobile applications should be improved by cutting down redundant functions to increase the work speed and user good experience to continue to use the smartphone applications (Li et al, ).…”
Section: Discussion Implication and Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…WhatsApp's other learning benefits include "immediate feedback to the problem, learning on the move, deeper clarity on issues, revision of previously learned topics, and the availability of learning materials all the time" (Bansal & Joshi, 2014, p. 5). Other aspects that users often appreciate include its simplicity to use and easy accessibility (Bansal & Joshi, 2014;Bonsu et al, 2021;Damayanti & Sibarani, 2020;Gon & Rawekar, 2017;Li et al, 2019). Moreover, using the application is cheap: its subscription was one dollar a year and then free since its incorporation into Facebook, and its data consumption and usage are much lower than other platforms, including LMSs (Bouhnik & Deshen, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%